The impact of value-based care models: The role of nurses and administrators in healthcare improvement - Alharbi, Ahmed Ali; Almalki, Mesfer Hamed M; Alhawit, Mohammed Eid; Alharbi, Awadh Mutab; Almutairi, Ghalib Talal; Alhejaili, Omar Lafi Olaythah; Albalaw, Mohammed Faraj; Alkhathami, Ali Mesfer; Binselm, Khalid Rashad A (International journal of health sciences, 2022)
Background: Value-based care (VBC) models, which emphasize bettering patient outcomes while cutting costs, are a revolutionary approach to healthcare delivery. VBC aligns incentives with quality rather than quantity by moving away from volume-driven care and toward outcome-focused treatments. The increasing prevalence of chronic illnesses, rising healthcare expenses, and inequalities in access to care are all addressed by these models. Patient-centered medical homes (PCMHs), bundled payment models, and accountable care organizations (ACOs) are important elements. Notwithstanding their potential, VBC models have drawbacks, including workforce preparedness, data system compatibility, and equitable application across a range of demographics. Aim: this work is to investigate the theoretical underpinnings, methods of implementation, and results related to VBC models. It also looks at the roles that nurses and health administrators have played in improving the planning, implementation, and assessment of these models. Methods: A thorough analysis of case studies, policy papers, and peer-reviewed literature was carried out. The operationalization of VBC, technology integration, and the contributions of interdisciplinary teams to raising the standard of care and reducing costs are the main topics of the analysis. Results: The results show that VBC models improve patient satisfaction, improve chronic illness management, and drastically lower hospital readmissions.